The question of evil and feminist legal scholarship - Murphy, Thérèse; Whitty, Noel (Springer, 2006)
In this article, we argue that feminist legal scholars should engage directly and explicitly with the question of evil. Part I summarises key facts surrounding the prosecution and life-long imprisonment of Myra Hindley, one of a tiny number of women involved in multiple killings of children in recent British history. Part II reviews a range of commentaries on Hindley, noting in particular the repeated use of two narratives: the first of these insists that Hindley is an icon of female evil; the second, less popular one, seeks to position her as a victim. In Part III, the article broadens out and we explain why we think feminist legal scholars should look at the question of evil. In large part, the emphasis is on anticipating the range of possible objections to this argument, and on trying to answer these objections by showing how a focus on evil might benefit feminist legal thinking – specifically in relation to the categories of perpetrator and victim and, more generally, in relation to laws motivated by a desire to secure women’s human rights.